Colloid cohydration and variable rate phenylephrine infusion effectively prevents postspinal hypotension in elective Cesarean deliveries - Indu Sen; Rozeeta Hirachan; Neerja Bhardwaj; Kajal Jain; Vanita Suri; Praveen Kumar (Wolters Kluwer Medknow Publications, 2013)
Background: Prevention of post-spinal hypotension in obstetric patients can be accomplished using intravenous fluid expansion and prophylactic use of sympathomimetic drugs. The affect of combination of colloids and phenylephrine infusion on maternal hemodynamics has not been widely studied and there is no consensus about the dosage required and time of starting its administration. Materials and Methods: This prospective, randomized, double-blind study enrolled 90 healthy term parturients undergoing elective Cesarean delivery under lumbar subarachnoid block (0.5% hyperbaric bupivacaine 10 mg with fentanyl 25 μg). Patients in Group A received prophylactic intravenous phenylephrine infusion (60 μg/minute) along with hydroxyl-ethyl-starch cohydration (6% HES 130/0.42;15 ml/kg) immediately after subarachnoid block. In Group B, patients received 6% HES cohydration and intermittent intravenous 50 μg boluses of phenylephrine. The efficacy of these in maintaining maternal SBP at 90-110% of baseline and neonatal well-being was evaluated. Results: In Group B, 75.5% of patients required rescue phenylephrine boluses to maintain SBP while maternal hemodynamics were well maintained in Group A and rescue drug was not needed. Reactive hypertension occurred in one patient (2.2%) and bradycardia in two patients (4.4%) in Group A. Six patients complained of nausea in Group B (13.3%) compared to one in Group A. All the newborns had normal Apgar scores and Umbilical arterial pH > 7.2. Conclusion: A combination of colloid cohydration and prophylactic phenylephrine infusion initiated at 60 μg/minute maintained maternal hemodynamics and neonatal well-being during Cesarean deliveries requiring minimum interventions by the anesthesiologist.